Occurrence of serrassalmidae hybrid fish in the amazon river basin, Brazil - de Lima, Felipe Pontieri [UNESP]; Mourão, Andrea Abrigato de Freitas [UNESP]; Nobile, André Batista [UNESP]; Freitas-Souza, Diogo [UNESP]; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fábio Porto [UNESP] (Oecologia Australis, 2019)
This study reports a case of occurrence of hybrid fish in the Amazon River basin, Brazil and attentive on to possible risks promoted with from crossbreeding between two species on local biodiversity. The specimen was collected in February/2016, and was evaluated showing dubious characteristics indicating the possibility of the occurrence of hybridization. Thus, fin specimen fragments were sampled and the genetic analyzes were performed. Our results indicated that the studied sample had a heterozygous electrophoretic profile revealing itself as a hybrid between Piaractus brachypomus and Colossoma macropomum being the second species the maternal parent.
Keywords: Crossbreeding; Genetic conservation; Genetic markers; Hybrid occurrence; Neotropical ichthyofaunal